2020
DOI: 10.3390/s20030635
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Semantic Segmentation and Depth Completion with Constraint of Boundary

Abstract: As the core task of scene understanding, semantic segmentation and depth completion play a vital role in lots of applications such as robot navigation, AR/VR and autonomous driving. They are responsible for parsing scenes from the angle of semantics and geometry, respectively. While great progress has been made in both tasks through deep learning technologies, few works have been done on building a joint model by deeply exploring the inner relationship of the above tasks. In this paper, semantic segmentation a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…In the context of image processing, tasks such as object detection and semantic segmentation have been tackled successfully (Yao et al, 2012), (Mohan and Valada, 2020), (Kim et al, 2020). Depth estimation and semantic segmentation have also been combined in one CNN as in (Eigen and Fergus, 2014), (Hazirbas et al, 2016), (Kendall et al, 2017), (Zou et al, 2020) Multi task networks have shown to achieve better results as whole in terms of their capability to provide a more holistic representation, but also the performance of each one of the tasks improves as a result of having a multi task CNN. Inspired by this approach, Liebel and Körner (2018) introduced the concept of "auxiliary tasks", they are side tasks that are less relevant for a given application but that potentially improved the performance of the core tasks.…”
Section: Multi Task Leaningmentioning
confidence: 99%
See 1 more Smart Citation
“…In the context of image processing, tasks such as object detection and semantic segmentation have been tackled successfully (Yao et al, 2012), (Mohan and Valada, 2020), (Kim et al, 2020). Depth estimation and semantic segmentation have also been combined in one CNN as in (Eigen and Fergus, 2014), (Hazirbas et al, 2016), (Kendall et al, 2017), (Zou et al, 2020) Multi task networks have shown to achieve better results as whole in terms of their capability to provide a more holistic representation, but also the performance of each one of the tasks improves as a result of having a multi task CNN. Inspired by this approach, Liebel and Körner (2018) introduced the concept of "auxiliary tasks", they are side tasks that are less relevant for a given application but that potentially improved the performance of the core tasks.…”
Section: Multi Task Leaningmentioning
confidence: 99%
“…Panoptic segmentation, for example, combines instance segmentation, object detection and semantic segmentation (Mohan and Valada, 2020), (Cheng et al, 2020), (Wang et al, 2020), (Weber et al, 2020). To our best knowledge, only few methods have combined semantic segmentation and depth completion (Sanchez-Escobedo et al, 2018), (Zou et al, 2020). As compared to other applications, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…RGB-GC [18] uses pre-trained semantic segmentation model on Cityscapes dataset [19]. SSDNet [20] and RSDCN [21] exploit the Virtual KITTI dataset [22] to learn the semantic labels of each pixel in dense depth. DeepLiDAR [1] jointly learns the depth completion and normal prediction tasks where the normal prediction module is pre-trained on a synthetic dataset generated from CARLA simulator [23].…”
Section: Related Workmentioning
confidence: 99%
“…This paper works on cityscape with depth dataset, which has many weakly labeled images. The challenge with working with 3D or 2.5D datasets is that they are not many accurate and highresolution datasets in that field [2,3].…”
Section: Introductionmentioning
confidence: 99%